Accessibility of E-Health Services for People With Disabilities - Bąkała, Anna Maria; Korczak, Karol (Dostępność serwisów z zakresu e-zdrowia dla osób niepełnosprawnych, 2010)
In this article the authors present the concept of online health services in Poland with taking the disabled people into account. In subsequent points of this paper there are presented: comparative analysis between e-health solutions in Poland and other European Counties, profile of selected e-health services which are or might be implemented in healthcare of people with disabilities, examples of existing e-health solutions in Poland, set of standards and requirements which have to be fulfilled by e-health services in order to be useful for the disabled and elderly people. In further work the authors plan to carry out a survey among this target group and explore real demand on e-health services.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 119, s. 31-37
Keywords: eHealth services; people with disabilities